2016
DOI: 10.1093/rheumatology/kew049
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between damage clustering and mortality in systemic lupus erythematosus in early and late stages of the disease: cluster analyses in a large cohort from the Spanish Society of Rheumatology Lupus Registry

Abstract: In a large cohort of SLE patients, cardiovascular and musculoskeletal damage manifestations were the two dominant forms of damage to sort patients into clinically meaningful clusters. Both in early and late stages of the disease, there was a significant association of these clusters with an increased risk of mortality. Physicians should pay special attention to the early prevention of damage in these two systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
7
26
2
1
Order By: Relevance
“…In the largest cluster, representing 73% of those analyzed (cluster 1), patients had little organ damage, thus corroborating previous SLE cohort studies . For instance, Pego‐Reigosa et al classified 3656 Spanish adults with SLE in the Spanish Rheumatology Society Lupus Registry (RELESSER) cohort into three damage clusters in 2015, and 2949 (80.6%) of them were assigned to the cluster showing the least damage. Toreente‐Segarra et al performed cluster analysis on 345 juvenile patients with SLE in the same cohort, finding that 72.7% of the patients were assigned to the cluster with least damage.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In the largest cluster, representing 73% of those analyzed (cluster 1), patients had little organ damage, thus corroborating previous SLE cohort studies . For instance, Pego‐Reigosa et al classified 3656 Spanish adults with SLE in the Spanish Rheumatology Society Lupus Registry (RELESSER) cohort into three damage clusters in 2015, and 2949 (80.6%) of them were assigned to the cluster showing the least damage. Toreente‐Segarra et al performed cluster analysis on 345 juvenile patients with SLE in the same cohort, finding that 72.7% of the patients were assigned to the cluster with least damage.…”
Section: Discussionsupporting
confidence: 75%
“…However, there were differences in patient selection between these three studies. Pego‐Reigosa et al recruited patients >16 years old, while Toreente‐Segarra et al recruited juvenile patients . We excluded patients with SLE whose disease duration was <5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, thrombosis is a well‐defined and important clinical complication in SLE . In particular, cerebral and cardiovascular ischemic events are major causes of irreversible damage and death in patients with SLE . Previous studies have found that the probability of arterial ischemic events is 5.1%‐8.5% within 5 years of diagnosis in patients with SLE .…”
Section: Discussionmentioning
confidence: 99%